Pentahelix approach in collaborative governance of social services and MSMEs in economic zone: A literature review from perspective of administrative law - Firzhal Arzhi Jiwantara; Bayu Karunia Putra (Green Governance: Exploring Politics, Social Justice, and the Environment, 2026)
Background: The development of the Gresik Regency Special Economic Zone (SEZ) in East Java has highlighted the need for integrated and collaborative governance in managing social services and supporting micro, small, and medium enterprises (MSMEs). Traditional top-down approaches in public administration have often limited stakeholder participation, while complex socio-economic challenges demand a multi-stakeholder strategy. The Pentahelix approach, which engages government, academia, industry, community, and media, offers a framework to enhance collaborative governance within the context of Indonesian administrative law. Methods: This study employs a systematic literature review of national and international journals, policy documents, and legal literature relevant to collaborative governance, MSME development, social services, and the Pentahelix model. A qualitative-descriptive approach is applied to identify patterns, opportunities, and constraints in implementing Pentahelix-based governance in SEZ contexts. Findings: The literature indicates that the Pentahelix approach facilitates multi-stakeholder coordination, transparency, and accountability in social service delivery and MSME support. In the Gresik Regency SEZ, collaboration among government agencies, local communities, academic institutions, private sectors, and media has shown potential in fostering inclusive economic development. However, challenges persist, including regulatory gaps, limited legal frameworks for stakeholder integration, and disparities in institutional capacities. Conclusion: The Pentahelix approach can strengthen collaborative governance in SEZs, aligning with principles of administrative law by promoting participatory decision-making, efficiency, and accountability. Effective implementation requires legal and institutional reforms to ensure sustainable coordination among diverse stakeholders. Novelty/Originality of this article: This article contributes conceptually by integrating the Pentahelix model with administrative law perspectives, offering a novel framework for understanding collaborative governance in Indonesian SEZs. It provides an interdisciplinary approach that combines legal, social, and economic considerations, which has been rarely explored in the literature on SEZ management and MSME development.